Use of Video and Robot Simulation at MIN 1 Kepahiang Bengkulu - Afizal Mayub; Rendy Wikrama Wardana; Henny Johan (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2022)
Community service activities are one of the university's tridharma activities that must be carried out by every lecturer, therefore lecturers of the Bengkulu University Master of Science Program in collaboration with teachers of Madrasah Ibtidaiyah Negeri 1 Kepahiang, Bengkulu on March 31, 2022 have carried out Community Service activities at Madrasah Ibtidaiyah Negeri 1 Kepahiang, Bengkulu. This collaboration is in the form of community service activities at Madrasah Ibtidaiyah Negeri 1 Kepahiang, Bengkulu with the title "Line Follower Robot Demonstration and Simulation to Increase Students' Interest in Learning Science at Home at Madrasah Ibtidaiyah Negeri 1 Kepahiang, Bengkulu. From these activities it can be concluded that; Robotics material delivered using interactive multimedia which includes lectures, virtual demos, animations, visualizations, and simulations as well as videos has proven to be successful in motivating students to care more about science in the motivated/cared category with a score of 3.85 on a scale of 1 -5.